Social Challenges Facing Academic Women - Najat Mohammed Faraj (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This research aims to identify the main social challenges facing academic women, it is qualitative method used scouting and thematice analysis, based on an in- depth interview, applied on a sample of (25) academic women at the University of Sulaimani, the research found that the academic w omen face a range of qualitative challenges in the university, family and community.